PENGHIJAUAN BATARAN SUNGAI BILAH DI DESA TEBING LINGGA HARA KECAMATAN BILAH HULU KABUPATEN LABUHANBATU - Fitra Syawal Harahap, Abdul Rauf, Sarifuddin, Abu Yazid (JURNAL BIMA, 2023)
Environmental greening is an effort to restore and improve the effectiveness of land so that it can function optimally well.environmental greening is an effort to deal with problems that arise in an area.in this environmental greening activity by utilizing land around the watershed Community service activity bar in the form of "counseling, lectures and training to provide understanding of land-based use technology Watershed management and symbolically tree management This community service activity involves the community in and the apparatus of Tebing Lingga Hara Village, Teaching Staff of the Agrotechnology Study Program, Faculty of Science and Technology, University of Labuhanbatu, Agrotechnology Study Program, Faculty of Agriculture, University of North Sumatra In the implementation of this activity, the community welcomed positively about the lectures and training given, which was shown by the discussion and the number of Questions raised by the community about watershed management to prevent flooding and pollution Riverbank management through planting trees based on watershed management technology are needed as one of the mitigation efforts against the flood disaster so that land use based on watershed management from upstream to downstream in this watershed area is very important for the achievement of sustainable development that prioritizes the achievement of social welfare and The economy of its people.